Jurnal Penyuluhan: Tingkat Kinerja Penyuluh Pertanian di Kabupaten Ogan Komering Ulu (OKU) Selatan - Tiara A.P Hernanda, Anna Fatchiya, Ma'mun Sarma (PPs ILMU PENYULUHAN PEMBANGUNAN IPB, 2015)
The existence of professional agri-extension worker is main extension’s issue to move it effectively and efficiently. Professionalism related with agri-extension worker’s extension performance, extension, extension workerperformance. The existing main problem is agri-extension worker’s performance in Indonesia is quite low. It is because of agri-extension worker has low individual quality, include in some district in South Sumatera.